ANALYSIS AND IDENTIFICATION SPIKING CHEMICAL COMPOUNDS RELATED TO CHEMICAL WEAPON CONVENTION IN UNKNOWN WATER SAMPLES USING GAS CHROMATOGRAPHY AND GAS CHROMATOGRAPHY ELECTRON IONIZATION MASS SPECTROMETRY - Harry Budiman (Universitas Gadjah Mada, 2007)
The identification and analysis of chemical warfare agents and their degradation products is one of important component for the implementation of the convention. Nowadays, the analytical method for determination chemical warfare agent and their degradation products has been developing and improving. In order to get the sufficient analytical data as recommended by OPCW especially in Proficiency Testing, the spiking chemical compounds related to Chemical Weapon Convention in unknown water sample were determined using two different techniques such as gas chromatography and gas chromatography electron-impact ionization mass spectrometry. Neutral organic extraction, pH 11 organic extraction, cation exchanged-methylation, triethylamine/methanol-silylation were performed to extract the chemical warfare agents from the sample, before analyzing with gas chromatography. The identification of chemical warfare agents was carried out by comparing the mass spectrum of chemicals with mass spectrum reference from the OPCW Central Analytical Database (OCAD) library while the retention indices calculation obtained from gas chromatography analysis was used to get the confirmation and supported data of the chemical warfare agents. Diisopropyl methylphosphonate, 2,2-diphenyl-2-hydroacetic acid and 3-quinuclidinol were found in unknown water sample. Those chemicals were classified in schedule 2 as precursor or reactant of chemical weapons compound in schedule list of Chemical Weapon Convention.